"Caballo": risk environments, drug sharing and the emergence of a hepatitis C virus epidemic among people who inject drugs in Puerto Rico - R. Abadie; K. Dombrowski (BMC, 2020)
Abstract Background Sharing drug injection equipment has been associated with the transmission of HCV among PWID through blood contained in the cooker and cotton used to prepare and divide up the drug solution. While epidemiologists often subsume this practice under the sharing of "ancillary equipment," more attention should be paid to the fact that indirect sharing takes place within the process of joint drug acquisition and preparation. Methods We employed an ethnographic approach observing active PWID (N = 33) in four rural towns in Puerto Rico in order to document drug sharing arrangements involved in "caballo", as this practice is locally known. We explored partners' motivation to engage in drug sharing, as well as its social organization, social roles and existing norms. Findings Findings suggest that drug sharing, is one of the main drivers of the HCV epidemic in this population. Lack of financial resources, drug packaging, drug of choice and the desire to avoid the painful effects of heroin withdrawal motivates participants' decision to partner with somebody else, sharing injection equipment-and risk-in the process. Roles are not fixed, changing not only according to caballo partners, but also, power dynamics. Conclusion In order to curb the HCV epidemic, harm reduction policies should recognize the particular sociocultural contexts in which people inject drugs and make decisions about risk. Avoiding sharing of injection equipment within an arrangement between PWID to acquire and use drugs is more complex than assumed by harm reduction interventions. Moving beyond individual risk behaviors, a risk environment approach suggest that poverty, and a strict drug policy that encourage users to carry small amounts of illicit substances, and a lack of HCV treatment among other factors, contribute to HCV transmission.